2023
DOI: 10.22541/essoar.167525247.77367925/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A precipitation isotopic response in 2014-2015 to moisture transport changes in the central Himalayas

Abstract: The effect of moisture transport on precipitation stable isotopes (δO and d-excess) in the central Himalayas is still unclear, although crucial to understand the climatic archives recorded in, e.g., ice cores. Here we present measurements of stable isotopes in precipitation at two stations (Yadong and Pali) in the central Himalayas during 2014-2015. Combined with simulations from the dispersion model FLEXPART, we investigate possible effects on precipitation stable isotopes related to changes in moisture sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Indeed, previous studies have used oxygen isotope measurements in precipitation (δ 18 O p ) in the Himalayas and adjacent regions to reveal moisture sources and moisture transport processes (Acharya et al., 2020; Adhikari et al., 2020; Axelsson et al., 2023; Chakraborty et al., 2016, 2022; Gao et al., 2011; Islam et al., 2021; Jeelani & Deshpande, 2017; Jeelani et al., 2018; Rahul & Ghosh, 2019; Ren et al., 2017; Sinha et al., 2019; Yu et al., 2016). For example, some studies have found that the δ 18 O p values on the southern slope of the Himalayas change significantly in response to different moisture transported by the westerlies and the Indian summer monsoon (Acharya et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have used oxygen isotope measurements in precipitation (δ 18 O p ) in the Himalayas and adjacent regions to reveal moisture sources and moisture transport processes (Acharya et al., 2020; Adhikari et al., 2020; Axelsson et al., 2023; Chakraborty et al., 2016, 2022; Gao et al., 2011; Islam et al., 2021; Jeelani & Deshpande, 2017; Jeelani et al., 2018; Rahul & Ghosh, 2019; Ren et al., 2017; Sinha et al., 2019; Yu et al., 2016). For example, some studies have found that the δ 18 O p values on the southern slope of the Himalayas change significantly in response to different moisture transported by the westerlies and the Indian summer monsoon (Acharya et al., 2020).…”
Section: Introductionmentioning
confidence: 99%